2016
DOI: 10.1073/pnas.1614266113
|View full text |Cite
|
Sign up to set email alerts
|

Thoughts about Dying in America : Enhancing the impact of one’s life journey and legacy by also planning for the end of life

Abstract: This Perspective offers a summary of the recommendations in the Institute of Medicine report Dying in America. How we die is a deeply personal issue that each of us will face. However, the approach to end-oflife (EOL) care in the United States needs improvement. Too frequently, healthcare delivery is uncoordinated and has many providers who are not adequately prepared to have meaningful conversations about EOL planning. This is amplified by payment systems and policies that create impediments, misunderstanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Social initiatives such as death cafes, health promoting palliative care, death education and compassionate communities are all examples of strategies that seek to ensure individuals and systems are aware of, and responsive to, end-of-life issues [ 13 ]. Many governments actively support palliative care programs and death awareness initiatives that address the anticipated increases in death and dying [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social initiatives such as death cafes, health promoting palliative care, death education and compassionate communities are all examples of strategies that seek to ensure individuals and systems are aware of, and responsive to, end-of-life issues [ 13 ]. Many governments actively support palliative care programs and death awareness initiatives that address the anticipated increases in death and dying [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Building community engagement with conversations about death and dying could encourage active involvement in decision-making, making end-of-life wishes known, and acceptance of death as an inevitable part of the life cycle (Chapple et al., 2017; Swerissen & Duckett, 2015; URBIS, 2016). Governments in many countries such as the United Kingdom and Australia actively support palliative care and advance care planning as well as death awareness initiatives such as death cafes and compassionate communities to improve community appreciation of dying and death as a normal part of the life continuum (Abel & Kellehear, 2016; Clark et al., 2017; Kellehear, 2016; Pizzo, 2016; URBIS, 2016). By being able to discuss death and dying in our families, communities and with our health-care providers, it is presumed we can develop the skills and competence to enable our own decision-making and support for others in our family and community (Noonan, Horsfall, Leonard, & Rosenberg, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Through this review, we identified 14 articles that discussed using the ethical will to address mortality or attitudes about death, which indicate that reflecting on meaning in life and articulating values may provide the writer a sense of life completion (Barnes et al, 1997; Wheeler and Farnsworth, 2000; Baines, 2003, 2004; Cole and Kloberdanz, 2003; Frank, 2003; Gessert et al, 2004; Alexander, 2006; Shultz, 2006; Hicks, 2008; Falkner, 2009; Williams et al, 2010; Martin, 2015; Grewe, 2017). The Dying in America report recommends patients, families, and providers prepare for death by having conversations throughout the life cycle, not just near the end of life (Pizzo, 2016). As the ability to plan and communicate effectively in the final days is not a guarantee, it is beneficial for individuals to begin planning for the end of life once they have an awareness of their mortality, which often occurs through the process of aging (Doka, 2015).…”
Section: Discussionmentioning
confidence: 99%